All hands on deck: A multidisciplinary approach to SARS-CoV-2-associated MIS-C. (28th April 2022) - Lopez, Alison A; Patel, Mona; Rayment, Jonathan H; Tam, Herman; Roberts, Ashley; Laskin, Samara; Tucker, Lori; Biggs, Catherine M
Abstract: Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a post-infectious complication of SARS-CoV-2 infection with overlapping features of Kawasaki disease and toxic shock syndrome. In May 2020, a provincial multidisciplinary working group was established in anticipation of emerging cases following the first wave of SARS-CoV-2 infections. Methodology: Our centre established a multidisciplinary working group for MIS-C cases in British Columbia. The group developed guidelines using the World Health Organization MIS-C case definition. Guidelines were updated using quality improvement methods as new reports and our local experience evolved. We included all children who were evaluated in person or had samples sent to our centre for MIS-C evaluation from May 2020 to April 2021. We prospectively collected patient demographics, clinical and laboratory characteristics, and treatment. Results: Fifty-two children were included. Eleven were diagnosed as confirmed MIS-C. Ten of the 11 MIS-C cases presented with shock. Gastrointestinal and mucocutaneous involvement were also prominent. Common laboratory features included elevated C-reactive protein, D-dimer, troponin, and brain natriuretic peptide. Four out of 11 (36%) had myocardial dysfunction and 3/11 (27%) had coronary artery abnormalities. All 11 patients had evidence of SARS-CoV-2 infection. Ten out of 11 (91%) received intravenous (IV) immunoglobulin and IV corticosteroids. Conclusion: Our provincial cohort of MIS-C patients were more likely to present with shock and cardiac dysfunction, require ICU admission, and be treated with corticosteroids compared to ruled out cases. Our working group's evolving process ensured children with features of MIS-C were rapidly identified, had standardized evaluation, and received appropriate treatment in our province.